2022
DOI: 10.1007/s00268-022-06439-7
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy Versus Cinacalcet for the Treatment of Secondary Hyperparathyroidism in Hemodialysis Patients

Abstract: Background Secondary hyperparathyroidism in patients with end stage renal disease on dialysis is associated with bone pain and fractures in addition to cardiovascular morbidity. Cinacalcet is the most commonly used drug to treat such patients, but it has never been compared to surgery. The goal of this study is to compare the long-term outcomes and survival between cinacalcet and parathyroidectomy in the treatment of secondary hyperparathyroidism in hemodialysis patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Even with the recently increased use of calcimimetics, surgery still plays an important role in the treatment of SHPT. While calcimimetic has been reported to have clinical benefits in terms of normalization of electrolytes and lowering parathyroid hormone (PTH) (3,4), its longterm survival benefit cannot be demonstrated by current evidence (5,6). In addition, most medical treatments will be ineffective after a period of application, and approximately 15% of the patients on dialysis will need parathyroidectomy after 5-10 years due to refractoriness to medical treatment or intolerance to side effects related to calcimimetics (1,5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Even with the recently increased use of calcimimetics, surgery still plays an important role in the treatment of SHPT. While calcimimetic has been reported to have clinical benefits in terms of normalization of electrolytes and lowering parathyroid hormone (PTH) (3,4), its longterm survival benefit cannot be demonstrated by current evidence (5,6). In addition, most medical treatments will be ineffective after a period of application, and approximately 15% of the patients on dialysis will need parathyroidectomy after 5-10 years due to refractoriness to medical treatment or intolerance to side effects related to calcimimetics (1,5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, patients with SHPT refractory to medical treatment exist ( 25 ). For these patients, PTx is the best treatment and should be indicated without delay to improve their QOL and reduce mortality ( 2 , 150 , 151 ). However, as the number of PTx for SHPT has decreased, consequently endocrine surgeons who have sufficient experience in performing PTx for SHPT are also decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a prospective cohort study from Japan, PTxtreated patients were compared with matched cinacalcet-treated patients, and PTx reduced the risk of mortality, most prominently in patients with intact PTH levels ≥500 pg/mL and those with serum calcium levels ≥10 mg/dL (2). A recent study of the United States Renal Data System and Japanese Society for Dialysis Therapy Renal Data Registry also showed superior 5-year and 6-year survival in the PTx-treated group compared with the cinacalcet-treated group (2,150). Additionally, from the viewpoint of QOL, the superiority of PTx compared with cinacalcet was demonstrated in a systematic review, where the physical component score and mental component score in the 36-item Medical Outcomes Study Short-Form Health Survey were significantly more improved in the PTx-treated patients than in the cinacalcet-treated patients (151).…”
Section: Calcimimetics Treatment Versus Ptxmentioning
confidence: 99%
“… 28 , 29 However, others stated that PTX offered no significant protection against cardiac complications in patients undergoing dialysis. 30 , 31 On the other hand, the EVOLVE trial found that cinacalcet decreased the frequency of cardiovascular complications in older patients with SHPT undergoing dialysis. Yet, this effect was not evident in younger patients.…”
Section: Discussionmentioning
confidence: 99%